Japanese eating and drinking culture in view of adab education concept as guided in relevant ahaadeeth muttafaqun ‘alayh - Andriana, Nesia; Rahman, Imas Kania; Muhyani, Muhyani (Ibn Khaldun Journal of Social Science, 2019)
Islamic society was born in an underdeveloped community with very limited natural resources of barren desert. The Arab Muslims conquered Mecca and started expanding their territory by conquering Rome in age just 26 years and Persia in 30 years. Followed by further expansion, Muslims conquered almost a third of the world and maintained the Islamic empire for about 8-10 centuries. At another point of history, Japan was also a country that has limited natural resources and frequently hit by natural disasters. Two of its major cities were destroyed by first developed atomic bombs in 1945; Japan declared its unconditional surrender in World War II and Japan became a country in ruins. However, it only took Japan a dozen years to recover, and even more, Japan has become a developed and politically stable country. This paper argues that the remarkable achievements made by both Japan and Islamic civilization resulted from developing and maintaining discipline daily habits from strong ethics and educational philosophies and concepts. Taking the most inevitable human daily habits, eating and drinking, as a focus, the writer conducted interview of some Japanese people and Indonesians who lived in Japan for over 10 years. The results of interview were compared with Rasoolullah peace be upon him and his companions' eating and drinking habits as reported in relevant ahaadeeth muttafaqun ‘alayh. This paper reveals similarities between the two societies' in their eating and drinking cultures and that discipline cultures, developed through strong education and embraced ethics have contributed to their remarkable human resources development and achievements.